The Administrative Leadership Role of the Heads of the Scout Division in the Performance of their Educational and Administrative Duties from the Perspective of the Scout Leaders - Noori Abbas, Riyadh; Sabur, Akeeljarh (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research is increasing to build and standardize the scale of the leadership role of the heads of Scout branches and to identify their levels. The researcher used the descriptive approach to suit the nature of solving the problem. The research society was randomly chosen by the researchers (80) leaders of Scouts leaders in middle schools. It also included the procedures for constructing the scale and then conducting the statistical procedures for extracting indicators of truthfulness, consistency and objectivity based on the results obtained. Multiple levels of heads of Scout branches have been shown and most have fallen into several levels.